Slum imaginaries and spatial justice in Philippine cinema - Macapagal, Katrina (Edinburgh University Press, 2021)
Outlining the rise of Philippine slums alongside the historical development of Philippine urban cinema, Slum Imaginaries and Spatial Justice in Philippine Cinema makes a novel contribution to the cinema-city nexus through its interdisciplinary framework of film studies and human geography.
Description based upon print version of record.
Keywords: Slums -- Philippines.; City planning -- Philippines.; City and town life in motion pictures.; Motion pictures -- Philippines -- History.; Vie urbaine au cinéma.; Cinéma -- Philippines -- Histoire.; PERFORMING ARTS / Film & Video / Direction & Production; City and town life in motion pictures; City planning; Motion pictures; Slums; Philippines; History